The Long-Term Impact of Childhood Stunting on Cognitive Development and Educational Outcomes - Aceng Ali Awaludin; Annisa Nurrachmawati; Arifah Devi Fitriani; Casia Reski (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze the long-term impact of stunting in childhood on cognitive development and educational attainment through a meta-analysis approach. Stunting, which is indicated by stunted linear growth due to chronic malnutrition, has long been associated with various negative consequences on health and social aspects. By systematically examining the results of quantitative studies from various countries and socio-economic contexts, this study identified a consistent pattern of association between stunting in early life and decline in cognitive function and academic achievement in adolescence and adulthood. Data were obtained from 25 studies that met the inclusion criteria published in the 2015 to 2024 range, and were analyzed using fixed-effect and randomized effects models with the help of the JASP application. The results of the meta-analysis showed that children who experienced stunting had an effect on cognitive and education with a pooled effect size value (Hedges' g = 1.10 t= 9.103; p < 0.001) with a high effect size category. These findings confirm that stunting not only has an impact on short-term physical conditions, but also has significant consequences for human resource development in the long term. Therefore, comprehensive nutrition and education interventions in early life are essential to break the chain of loss due to stunting.